Preparation and characterization of UV-curable polymeric support for covalent immobilization of xylanase enzyme - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (ELSEVIER, 2011)
The hydroxyl group of poly(ethylene glycol) monoacrylate (PEGMA) was activated by 1 1'-carbonyldiimidazole (CDI) and then a xylanase enzyme was immobilized to amine active PEGMA UV-curable polymeric support formulation was prepared by mixing the xylanase bonded PEGMA aliphatic polyester 2-hydroxyethyl methacrylate (HEMA) poly(ethylene glycol) diacrylate (PEGDA) and photoinitiator After UV irradiation the enzymatic activity of the polymeric matrix was evaluated and compared with the corresponding free enzyme By immobilization the temperature resistance of the enzyme was improved and showed maximum activity at 60 C pH dependent activities of the free and immobilized enzymes were also investigated and it was found that the pH of maximum activity for the free enzyme was 60 while for the optimal pH of the immobilized enzyme was 65 The immobilized enzyme retained 75% of its activity after 33 runs The morphology of the polymeric support was characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) coupled with SEM was used to explore the chemical composition The results have confirmed the evidence of enzyme in the structure of the polymeric material (c) 2010 Elsevier B V All rights reserved
Keywords: Xylanase; Enzyme immobilization; Polymeric support; UV-curing; 1 1 '-carbonyldomidazole; CANDIDA-RUGOSA LIPASE; OPTIMIZATION; ACTIVATION; STABILITY; MEMBRANES